2017
DOI: 10.3141/2650-07
|View full text |Cite
|
Sign up to set email alerts
|

Time Use, Disability, and Mobility of Older Americans

Abstract: This study explored how disability, mobility, social and leisure engagement, and travel behavior influence older people’s life satisfaction. The study used the 2013 Disability and Use of Time data for people ages 50 years and older, many of whom reported physical impairments. The study developed a model that related life satisfaction with various time use, disability, and mobility variables. Summary statistics of time use showed that as people aged, they spent more time on solitary, passive leisure activities;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…As a major Midwestern city that is more auto-dependent than coastal cities such as New York, San Francisco and Boston, the analysis of the travel behaviour of older adults can offer valuable insights to numerous US cities with a similar urban form and transportation network. (Hess and Russell, 2012;Fordham et al, 2017;Li and Tilahun, 2017). Both surveys provide detailed information on respondents' individual and household characteristics, transportation mode choices and impressions regarding amenities, services, infrastructure and barriers within their neighbourhood.…”
Section: Methodsmentioning
confidence: 99%
“…As a major Midwestern city that is more auto-dependent than coastal cities such as New York, San Francisco and Boston, the analysis of the travel behaviour of older adults can offer valuable insights to numerous US cities with a similar urban form and transportation network. (Hess and Russell, 2012;Fordham et al, 2017;Li and Tilahun, 2017). Both surveys provide detailed information on respondents' individual and household characteristics, transportation mode choices and impressions regarding amenities, services, infrastructure and barriers within their neighbourhood.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses using American Association of Retired Persons (AARP) data found that a smaller social network, lower socio-economic status, lack of transportation options, and living in an unwalkable location are all connected to a lower quality of life among seniors (Kim & Ulfarsson, 2013;Kim, 2011b). The literature also suggests that the health impacts of aging affect travel and, in turn, lead to diminished life satisfaction (Enam, Konduri, Eluru, & Ravulaparthy, 2017;Li & Tilahun, 2017). By contrast, an active lifestyle and traveling to socialize can improve quality of life in older adults (Chen et al, 2020;Ravulaparthy, Konduri, & Goulias, 2016).…”
Section: A Population Aging In Place and Impacts Of Diminished Travelmentioning
confidence: 99%
“…Non-driving seniors and individuals with lower income have the smallest activity area compared to those who drive (Kim & Ulfarsson, 2015) in that driving extends accessibility to various destinations (Figueroa, Nielsen, & Siren, 2014;Hess, Norton, Park, & Street, 2016). In addition, driving is associated with increased life satisfaction for many seniors (Li & Tilahun, 2017). Many factors are associated with seniors' driving needs such as living in a location for more years (Hess et al, 2016) or living in suburbs or exurbs (Kim & Ulfarsson, 2015).…”
Section: Seniors' Travel Behaviorsmentioning
confidence: 99%
“…Older adult emotions are positively affected by mobility factors, such as vehicle availability or being able to drive or walk to seniors’ centers and meet with friends. Lower levels of mobility due to physical impairments, sedentary lifestyle, and long hours of TV viewing as well as assistance with activities of daily living (ADLs) are positively associated with heightened depressive symptoms [ 32 ]. As mobility relates to motor control and maintenance of brain volume, being able drive or workout with friends promotes functional independence [ 33 ].…”
Section: Introductionmentioning
confidence: 99%